PENGELOLAAN SANGGAR SENI KUDA LUMPING KARYA BARU DI KAMPUNG MAREDAN BARAT KECAMATAN TUALANG KABUPATEN SIAK - Natasya, Vivi Aprilia; Maemunaty, Titi; Ayub, Daeng (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research examines the management of the New Lumping Karya Horse Art Studio in Maredan District Tualang Regional Siak and in that management there is planning, organizing, implementing, monitoring, evaluating, funding, marketing in managing the New Lumping Karya Horse Art Studio. The purpose of this study was to determine and analyse how the management of the New Lumping Karya Horse Art Studio In the Village of West Maredan District Tualang Regional Siak. This type of research is descriptive with a qualitative approach, in which the data collection process is carried out by interviewing 5 subjects, namely supporting informants, control informants, core informants 1, core informants 2, core informants 3 with accompanying documentation. Based on the results of interviews, researchers found 7 indicators, namely: (1) planning, (2) organizing, (3) implementation, (4) monitoring, (5) evaluation, (6) funding, (7) marketing. The study of the 7 indicators is very useful to understand how the appropriate stages of the implementation process are in carrying out the management of the New Lumping Karya Horse Art Studio.Key Word: Management, Lumping Horse Art Studio